Similar Proportions of Stool Specimens From Hospitalized Children With and Without Diarrhea Test Positive for Clostridium difficile. Issue 3 (March 2015) - Leibowitz, Jill; Soma, Vijaya L.; Rosen, Lisa; Ginocchio, Christine C.; Rubin, Lorry G.
Abstract : Background: Many laboratories use polymerase chain reaction (PCR)-based assays to detect the Clostridium difficile toxin B gene ( tcd B) in stool. However, PCR testing experience in pediatric patients is limited. We compared the detection of C. difficile by PCR in hospitalized children with and without diarrhea. Methods: Stool samples from patients aged 1–18 years with diarrhea (symptomatic) and from patients without diarrhea (asymptomatic) were tested for C. difficile tcd B using a commercial PCR assay. Samples were cultured for C. difficile using standard techniques with tcd B PCR and cytotoxicity assays performed on C. difficile isolates. Demographic, clinical and laboratory data were abstracted. Categorical and continuous variables were compared between the 2 groups using Fisher Exact test and the Mann–Whitney test, respectively. Results: Thirty-five of 188 (19%) stool samples from symptomatic patients and 18 of 74 (24%) samples from asymptomatic patients were positive by PCR ( P = 0.31). Among PCR-positive patients, symptomatic patients had a significantly higher proportion of subjects who received antimicrobials in the preceding 30 days ( P = 0.04) and a greater number of preceding antimicrobial days than did asymptomatic patients ( P = 0.02) but were comparable with respect to the other variables analyzed. Conclusions: C. difficile PCR assays are frequently positive in hospitalized children both with and without diarrhea. As we observed a high level of toxigenic C. difficile colonization in children, our findings suggest that a positive C. difficile PCR result in a child with diarrhea should be interpreted with caution.